Characterizing the membrane-disruptive behavior of dodecylglycerol using supported lipid bilayers - Yoon, Bo Kyeong (2021)
Monoglycerides are esterified adducts of fatty acid and glycerol molecules that disrupt phospholipid membranes, leading to a wide range of biological functions such as antimicrobial activity. Among monoglycerides, glycerol monolaurate (GML) exhibits particularly high antimicrobial activity, although enzymatic hydrolysis of its ester group can diminish potency. Consequently, there have been efforts to identify more chemically stable versions of GML, most notably its alkylglycerol ether equivalent called dodecylglycerol (DDG). However, despite high structural similarity, biological studies indicate that DDG and GML are not functionally equivalent and it has been speculated that the two compounds might have different interaction profiles with phospholipid membranes. To address this outstanding question, herein, we employed supported lipid bilayer (SLB) platforms to experimentally characterize the interactions of DDG with phospholipid membranes. Quartz crystal microbalance-dissipation experiments identified that DDG causes concentration-dependent membrane morphological changes in SLBs and the overall extent of membrane remodeling events was greater than that caused by GML. In addition, time-lapsed fluorescence microscopy imaging experiments revealed that DDG causes extensive membrane tubulation that is distinct from how GML induces membrane budding. We discuss how differences in the head group properties of DDG and GML contribute to distinct membrane interaction profiles, offering insight into how the molecular design of DDG not only improves chemical stability but also enhances membrane-disruptive activity.